El laboratorio virtual para el desarrollo de los trabajos experimentales de Química General con los estudiantes de segundo semestre de la carrera de Biología, Química y Laboratorio, enero 2017 – agosto 2017 - Chasi Amangandi, Miguel Angel (2017)
This research was developed at the National University of Chimborazo in the Faculty of Humanities and Technologies Education, in Biology, Chemistry and Laboratory major with the second semester students in the subject of General Chemistry. The problem is centered in the difficulty that learners present when developing experimental practices of Chemistry - number of students, availability of materials and adequate spaces. The objective is to justify the importance of virtual laboratories in the development of the experimental works of General Chemistry with the second semester students of the Biology, Chemistry and Laboratory major, January - August 2017. The applied methodology consisted of a non experimental design, The level of research was descriptive, using the technique of the survey with its instrument the questionnaire. A population of 23 students was collected for the data collection. The result of the research shows that the Virtual Labs are flexible, accessible and adaptive to the current context considering virtual tools of great importance in the execution of the experimental works in General Chemistry, in addition they facilitate the process of teaching - learning providing skills Communicative, collaborative and creative, acquiring the student a continuous and integral development.